2023
DOI: 10.1021/acssynbio.3c00375
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Gene Circuits Combining CRISPR Interference and CRISPR Activation in E. coli: Importance of Equal Guide RNA Binding Affinities to Avoid Context-Dependent Effects

Içvara Barbier,
Hadiastri Kusumawardhani,
Lakshya Chauhan
et al.

Abstract: Gene expression control based on clustered regularly interspaced short palindromic repeats (CRISPR) has emerged as a powerful approach for constructing synthetic gene circuits. While the use of CRISPR interference (CRISPRi) is already well-established in prokaryotic circuits, CRISPR activation (CRISPRa) is less mature, and a combination of the two in the same circuits is only just emerging. Here, we report that combining CRISPRi with SoxS-based CRISPRa in Escherichia coli can lead to context-dependent effects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The use of orthogonal dCas9 genes has been previously reported in yeast and mammalian cells to engineer repression, activation, and deletion; , however, to our knowledge, the evaluation of orthogonality between different dCas9 systems is still unreported in bacteria, in which multitarget or multifunctional regulations (i.e., repression and induction in the same cell) have been successfully engineered using a single dCas9 gene. , The described data demonstrate the orthogonality between two CRISPRi repression systems to expand bacterial synthetic circuit design toolboxes.…”
Section: Resultsmentioning
confidence: 68%
“…The use of orthogonal dCas9 genes has been previously reported in yeast and mammalian cells to engineer repression, activation, and deletion; , however, to our knowledge, the evaluation of orthogonality between different dCas9 systems is still unreported in bacteria, in which multitarget or multifunctional regulations (i.e., repression and induction in the same cell) have been successfully engineered using a single dCas9 gene. , The described data demonstrate the orthogonality between two CRISPRi repression systems to expand bacterial synthetic circuit design toolboxes.…”
Section: Resultsmentioning
confidence: 68%
“…Still, we found that txCRISPRi resulted in no differential LNT production relative to the txCRISPRa-only strain ( Supplementary Figure S10 ). One possible explanation for the lack of improved LNT production from these CRISPRi targets is that the expression of additional gRNAs leads to competitive effects, in which gRNAs with varying binding affinities are competing for a limited pool of dCas9 ( 57 , 58 ). However, the LNT titers are similar between the conditions with no CRISPRi gRNA and the non-targeting gRNA.…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed an approach for the construction of multi-gene CRISPR transcriptional control programs in bacteria, with activation (CRISPRa) or repression (CRISPRi) functions specified through the regulated expression of multiple guide RNAs (gRNAs) 11,12 . Recent demonstrations of dynamic multi-layer CRISPRa/i gene regulatory network designs in E. coli 13,14 and CRISPR-based metabolic pathway engineering in the soil microbe Pseudomonas putida [15][16][17] highlight the versatility of these systems for programmable multi-gene control. However, gaps in knowledge and technique continue to prevent the routine design of CRISPRa/i programs capable of quantitatively tuning activated expression from multiple bacterial genes at the same time 9,18 .…”
Section: Introductionmentioning
confidence: 99%